Ceramide synthase 4 is highly expressed in involved skin of patients with atopic dermatitis. (29th June 2016) - Ito, S.; Ishikawa, J.; Naoe, A.; Yoshida, H.; Hachiya, A.; Fujimura, T.; Kitahara, T.; Takema, Y.
Abstract: Background: Ceramide is a crucial lipid in the stratum corneum (SC) which maintains the barrier function and hydration of the skin. In atopic dermatitis (AD) patients who have defective skin barrier function, ceramide levels are altered. We previously reported that although the amount of total ceramide was lower in involved skin compared with uninvolved skin of AD patients and with healthy control skin, the amounts of smaller ceramide species of Cer[NS] (<40 total carbons, which are total carbons of both sphingoid base and amide‐linked fatty acid), especially Cer[NS] with 34 total carbons (C34‐Cer[NS]), were higher. However, the enzyme(s) that produces the higher levels of smaller ceramide species in involved skin of AD patients was unclear. Objective: To identify the enzyme(s) that produces higher levels of smaller ceramide species of Cer[NS] in the involved skin of AD patients. Methods: Eight female Caucasian subjects who were diagnosed with AD on their arms (age range: 21–45 years) were enroled in this study. We compared ceramide levels in the SC and the expression levels of enzymes involved in ceramide metabolism using real‐time PCR and immunohistochemistry between involved and uninvolved skin of AD patients. Results: Level of mRNA encoding ceramide synthase 4 (CERS4), which is one of the enzymes that synthesize ceramide from a sphingoid base and an amide‐linked fatty acid, was significantly higher in involved skin than in uninvolved skin ( P < 0.01). Additionally, the protein expression level of CERS4 in the epidermis was also higher in involved skin compared with uninvolved skin. The expression level of CERS4 correlated with the amount of C34‐Cer[NS] ( P < 0.01) and the skin hydration value ( P < 0.05). Conclusions: The elevated expression level of CERS4 contributes to the increase of C34‐Cer[NS] and the impaired SC barrier function in involved skin of AD patients.